Cash conversion cycle and firm's performance: evidence from steel industry in Thailand / Muhammad Amierrul Zainal Hamelee - Zainal Hamelee, Muhammad Amierrul (2017)
The aim of this paper is to prove the impact and all the effects of cash conversion cycle (CCC) on the profitability of firms. Using data from an extensive sample of Thailand steel industry over the 2012 - 2016 periods. This study absolutely concerned about evaluating how cash conversion cycle affects the profitability. Thus, to obtain recent and fresh result about this issue, new variables are introduced to be observed in this study. It includes cash conversion cycle, current ratio, debt ratio and firm size. The study offers proof that CCC significantly will affect profitability. Nevertheless, the limitation that found in this study is on the scope of study itself, as it is on steel companies in Thailand, there are some limitations met in examining the industry as there is insufficient amount of sources for researcher to collect information and obtain further insights.